Serangga Polinator (Lepidoptera: Superfamili Papilionoidea) Guna Mendukung Pertanian Berkelanjutan di Lahan Agro-Ekosistem - Daawia, Daawia; Dianingsih, Nurlita; Numberi, Yuliandra M.; Suhartawan, Bambang (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
This research aimed to determine the role of butterflies as pollinators of various horticultural plants and wild flowering plants at the agro-ecosystem in Arso District, Keerom Regency. Data collection on butterfly nectar sources used the Visual Count Method and All Out Search Method (AOSM) at Arso District every week for 4 months (May-August 2023). From the survey results, it was discovered 32 species of butterflies of Superfamily Papilionoidea that consisted of Paplionidae (9 species), Pieridae (6 species), Nymphalidae (12 species) and Lycaenidae (5 species). These butterflies visited flowering plants as a source of nectar. It was found 25 species of flowering plants consisting of 10 families which were sources of nectar for butterflies, namely Asteraceae, Rubiaceae, Malvaceae, Lamiaceae, Orchidaceae, Verbenaceae, Fabaceae, Amaranthaceae, Cucurbitaceae, and Rutaceae. The flowering plants most visited by butterflies were Bidens pilosa (15 species), Stachytarpheta urticaefolia (14 species), and Lantana camara (10 species). Asteraceae is the family of flowering plants most visited by butterflies, recorded 19 species. Butterflies have an important role in helping to pollinate wild flowering plants and horticultural plants in the agroecosystem in Arso District. The Papilionidae and Nymphalidae families were efficient pollinators because of their high mobility and large body size which could transfer more pollen from one flower to another. Pieridae visit more flowering plants than any other butterfly family, of the 25 species of flowering plants, 23 of them are visited by Pieridae. Even though the Lycaenidae are less efficient in helping pollination because they visit more limited flowers as a result of their limited body size and flight power, especially plants that had small flowers such as bitter melon, long beans and cucumbers. Key words: Lycaenidae; Nymphalidae; pollinator; Papilionidae; Pieridae.